The range order of a product of i transformations from a finite full transformation semigroup

  • PDF / 181,895 Bytes
  • 6 Pages / 468 x 684 pts Page_size
  • 96 Downloads / 157 Views

DOWNLOAD

REPORT


RESEARCH ARTICLE

THE RANGE ORDER OF A PRODUCT FROM A FINITE

OF

i

TRANSFORMATIONS

F U L L TRANSFORMATION

SEMIGROUP

Peter M. Higgins Communicated

by N.R. Reilly

Let

T denote the full transformation semigroup on a finite set n {l,2,...,n}. Denote the range of u e T by Vs. Let X. be n 1 the random variable with value n-llv~l~2...ui I t where C~l,C~ 2 . . . .

,c~ i

member of

T

allowed). x2

are

are

n In

1 - e

randomly

chosen

is equally

likely

-i

members

of

T

(meaning

n

that

to be chosen and repetitions

each

are

[2 ] it was sho_w~ that the limiting means of X1 (e---l) and 1 - e respectively. The natural

extension

of this result is g i v e n

and take

M 0 = i.

below.

Denote

lim

EX i

by

and

Mi

-S. THEOREM

Mi+ 1 = 1 -

and in addition

We approach

1.

for

all

M. ~ 2/i

as

i ยง ~.

chosen

exs,

from

IVUl~2...Ui+ll

number of non-empty balls

i

= O,

the proof by first supposing

been randomly value of

e

Tn

we obtain

n

and

m

by

From

< 1/n

= r. as

The X,

in w h i c h

the r

[i, Ch. II, Sec.ll,

that for

=: Pm(r,n)

=

(_l)v(n-m) (n-m-9) n and

m-i

respectively

Pm l (r,n-l)

= m

() ~n

r Pm(r,n )

n

31

(i)

.

r

n-I

-

21.

el,~2,...,u i have

IV~l~2...~il

boxes.

V=0 n

, VarX.

in a ball tossing experiment

1 ( m K n, P ( X = n-m)

Replace

...

then has the same distribution

boxes

n-m (n) X

2,

that

and that

are tossed at random into 8 and 9]

1,

in

(i) to obtain (2).

HIGGINS

Sum equation

(2) o v e r

m

to g e t n Z m Pm(r,n), m= 1

i = In (n-~)r-

o r in o t h e r w o r d s E X = n - n(n-l) r n A l l the

factorial

manner.

moments

re(m-l) n(n-l)

1 n (n-l)

1

Since

Y-n-X

can b e

calculated

in t h i s

In p a r t i c u l a r

Pm-2(r'n-2)

=

of

(3)

E{Y(Y-I)}

VarX

)r

Pm(r,n) , whence

n

( n )r ~

% m (m-l) P m (r'n) m=l

= n(n-l)

= VarY

( n ~

(n-2)r n

we g e t

V a r X = n(n-l)

(n-2)r + n ( n - l ) r n n

_ n2(n-l)2r n

or VarX - n((l

- 2)r n

_

terms

Note the

first a n d

third

negative

while

second

the

V a r X < n,

independently

The

statement

first

result

follows

the s t a t e m e n t

from

+

is b o u n d e d

o f the r a n k

a n d the

hand side

of

(4)

(4) are

Thus w e h a v e

r .

VarX. < i/n. i

Therefore

can now be proved.

i = k - i,

Inequality

(i - 2) r n

-

a b o v e b y one.

(3) u p o n p u t t i n g for

(i - l ) r n

o f the r i g h t

of t h e t h e o r e m

holds

By Chebyshev's

(i - l) 2r) n

r = n. k ~ i.

fact t h a t

Assume Let ~

For

i = 0 the

inductively

e, 6 > 0 < i/~n

that

b e given.

it f o l l o w s

Xk t h a t for

n

sufficiently

large

The t h e o r e m

is n o w

obtained

E(Xk+llXk

~)

-

=

arbitrarily

=

small

1

(i

-

interval

P(I~_

by noting

l)nX (~

where

- ~_I9 < 6) > 1 - e.

that X

almost

- 6, M k + 6)

32

surely

lies

for s u f f i c i e n t l y

in the l a r g e n.

HIGGINS

F r o m w h a t has b e e n p r o v e d x > 0

w e see that the s e q u e n c e

decreasing of

a n d the fact t h a t

sequence -x = 1 - e

f(x)

which must

iM. (i